Wind tunnel experimental study on static aerodynamic performance of SB-VAWT without intermediate support axes - Zhang, Huawu; Hu, Yihuai (Frontiers in Energy Research, 2023)
Wind power generation is considered an effective way for ships to harness wind energy, and the aerodynamic characteristics of wind turbines determine wind energy utilization and efficiency. However, traditional vertical axis wind turbines have intermediate shafts and support rods, which result in large negative effects in the research of the wind turbine aerodynamic characteristics. To address this issue, a Straight-Bladed Vertical Axis Wind Turbine (SB-VAWT) without intermediate support axes is proposed. The turbine can flexibly change the number of blades, rotor diameter, and installation position of blades. The static aerodynamic performance of the wind turbine with different combinations was tested in a wind tunnel laboratory at 10 m/s. The results show that the radius of the wind turbine has a greater effect on the drag coefficient for the same number of blades, with an inverse relationship between the drag coefficient and radius, and a positive association between lift coefficient, static torque coefficient, and radius. The drag coefficient is proportional to the number of blades at the same radius, while the static torque coefficient is inversely proportional to the number of blades. According to the results, placing the initial location in the azimuth range between 30° and 50° can obtain the maximum initial starting torque. Moreover, a wind turbine with a radius of 16 cm can achieve a higher average torque. Changes in the number of blades can significantly impact turbine properties, resulting in wind turbines with distinct features.